2017
DOI: 10.1109/tro.2017.2665664
|View full text |Cite
|
Sign up to set email alerts
|

FreMEn: Frequency Map Enhancement for Long-Term Mobile Robot Autonomy in Changing Environments

Abstract: Abstract-We present a method for introducing representation of dynamics into environment models that were originally tailored to represent static scenes. Rather than using a fixed probability value, the method models the uncertainty of the elementary environment states by probabilistic functions of time. These are composed of combinations of harmonic functions, which are obtained by means of frequency analysis. The use of frequency analysis allows to integrate long-term observations into memoryefficient spatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 36 publications
0
122
0
Order By: Relevance
“…Unlike the aforementioned works, which focused on the spatial structure and appearance aspects of the changes observed, other authors [2], [15], [16], [3], [5] focused on modelling the temporal aspects. For example, [2] and [15] represent the environment dynamics by multiple temporal models with different timescales, where the best map for localisation is chosen by its consistency with current readings.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the aforementioned works, which focused on the spatial structure and appearance aspects of the changes observed, other authors [2], [15], [16], [3], [5] focused on modelling the temporal aspects. For example, [2] and [15] represent the environment dynamics by multiple temporal models with different timescales, where the best map for localisation is chosen by its consistency with current readings.…”
Section: Related Workmentioning
confidence: 99%
“…The aforementioned approaches demonstrated that considering temporal aspects (and especially their persistence and periodicity) in robotic models improves not only mobile robot localisation [5], [3], [2], but also planning [17], [18] and exploration [19]. However, these temporal representations were tailored to model the probability of a single state over time, and thus were applied only to individual components of the discretised models, e.g.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used in many applications, such as in occupancy grids to compress long-term observations [10], in topological maps to improve robotic search [11], and in path planning [12]. The technique can be applied to all models that represent the world as a set of independent components with binary states [13]. We extend the technique by employing both Poisson processes as the counting model to replace the binary states of FreMEn and a new way of selecting the most prominent frequency components of the Fourier spectrum.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore there is no surprise that up to the moment of writing of this paper there were many papers just in this year dealing with the interaction between a mobile robot and its interface with humans and their environment [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. One of the main means of interaction is vision.…”
Section: Introductionmentioning
confidence: 99%